(untitled) (Global Journal of Management and Business Research, 2016)
This paper investigates the role of IT governance and business-IT alignment in company divestment Divestments are described as strategy s missing link Divestment is commonly an affirmation of dynamic volatile internal or external business landscapes and the aspiration is consistently to bolster and underline the company s efficacy and performance Divestiture will oblige enactment of the company business strategy and it thus includes a strategic proportion Divestment can be a pertinent and lucrative strategy The successful accomplishment of a divestiture is generally calculated by the dimension of accomplishment in realizing the elemental strategic goal that the company set out to achieve when adopting a divestment strategy The paper will also highlight the relevance of Information Technology IT in a divestment strategy by discussing the habits of an effective IT governance model and the business-IT alignment levels and approaches to support the company s strategy and goals even if it is a divestment strategy